Upaya Pembinaan Perawat Di Rumah Sakit Ngesti Waluyo Parakan Temanggung Jawa Tengah - Simamora, Roymond H (Jurusan Keperawatan FIKES UNSOED, 2013)
This study aims to provide an overview of the planning process, implementation, and evaluation of coaching the professional attitudes of nurses in nursing service and identifying factors that influence the (un)professional attitude. This study used qualitative approach with a case study design. Subjects were 7 managers, 12 nurses and 8 patients who were recruited purposively. The data obtained were analyzed qualitatively through data reduction. In this hospital, guidance and development of attitudes did not exist but only in form of problems solving or reprimanding nurses only when they committed unprofessional attitudes. There was no standard or procedures for ethical guideline in this hospital. Coaching is generally done only in the form of oral face to face reprimanding. In evaluatif the coaching there was no standard or indicators such as complaints reduction from patients, increased performance, and better work, not repeating the same mistakes, and able to communicate and cooperate well. The identified factors which affected The construction of unprofessional behavior of nurses were the burden of nurses, Works environment, the internal motivation of nursing staff, the readiness of managers to nurture, and support from hospital management, and the welfare of the employees.